A Local Development Strategy: Community of San Luis Sesma, Mexico - Lugo-Morin, Diosey; Rosales, Rubén; Porquillo, Elisa; Galicia, Cecilia (MAD, 2006)
<!–[if gte mso 9]> Normal 0 21 false false false ES-TRAD X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> The present work analyzes the problematic one that keeps San Luis Sesma, community pertaining to the municipality of Mazapiltepec de Juarez, Puebla from a perspective of analysis, that allows us to include/understand the relation that keeps this community with its territory and that has stayed relatively isolated and marginalized, with a autarquica production of the farming systems, in addition to an institutional disarticulation, the growth of the migration towards other regions like subsistence strategy and to increase the familiar entrance in the incorporation towards other sectors. Before previous a group of students of Postgraduate in Agricultural Strategies Regional of the School of Postgraduates, Puebla Campus, they find an opportunity to propose short strategic attachment lines and medium term in the farming sector, on the basis of the natural resources available of the community, and the involvement of the social actors through the organization like articulator element of the group of producers d and San Luis Sesma and the participation of the governmental institutions by means of the state and federal programs that promote a transference of technology, experiences, of resources, in such a way that all the previous one I helped to increase the production systems and therefore one is reflected in better income for the producers of the community.